The effect of ex-add learning techniques on critical thinking skills and pedagogic competence of Islamic education students - Mahfudz Mahfudz; Sukarno Sukarno (Intelektual Pustaka Media Utama, 2023)
This study aimed to determine the effect of explain-analysis-doing-discussion or known as ex-add learning techniques on critical thinking skills and pedagogic competence of Islamic religious education students at State Islamic University (UIN) Sulthan Thaha Saifuddin Jambi and at UIN Raden Fatah Palembang, Indonesia. The approach used quantitative with quasi-experimental techniques. The number seen in this study was 31 students from UIN Sulthan Thaha Saifuddin Jambi. The data were obtained using tests, namely pretest, and posttest. The test instrument was in the form of multiple-choice questions, each consisting of 40 questions. Data analysis was carried out using percentage techniques, N-gain analysis, and a T-test. Based on the data and discussion that has been done, it can be concluded that the ex-add technique in ‘learning methods and strategies’ can increase critical thinking skill (CTS) and pedagogic competence (PC) respectively by 78 .23% in the ‘high’ category and 59.81% in the ‘medium’ category. This is reinforced by the results of the T-test that both variables obtain a value (2-tailed) of 0.0000.05. This means that there is an average difference between the pretest and posttest scores for each variable. In other words, it can be said that the increase in student CTS and PC after participating in learning with the ex-add technique is significant.